2019
DOI: 10.3390/en12234560
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Influence of Mechanical Draft Wet-Cooling Towers on the Cooling Performance of Air-Cooled Condenser with Complex Building Environment

Abstract: In air-cooled power units, an air-cooled condenser (ACC) is usually accompanied by mechanical draft wet-cooling towers (MCTs) so as to meet the severe cooling requirements of air-cooling auxiliary apparatuses, such as water ring vacuum pumps. When running, both the ACC and MCTs affected each other through their aerodynamic fields. To make the effect of MCTs on the cooling performance of the ACC more prominent, a three-dimensional (3D) numerical model was established for one 2 × 660 MW air-cooling power plant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…CFD modeling has been used to further investigate the plume volume, length, and width with and without a wind velocity, which has also inspired other studies on plume volume flux [3][4][5][6]. Takata et al used a Reynolds-averaged Navier-Stokes model to predict wind effects on a rising visible plume from an MDCT in the absence of nearby buildings [3], while Fan et al similarly modeled an MDCT near a complex building environment [7]. Chahine et al simulated plume dispersals from four large, collocated natural draft cooling towers to determine the long-range visual impact of the facility [8].…”
Section: Introductionmentioning
confidence: 99%
“…CFD modeling has been used to further investigate the plume volume, length, and width with and without a wind velocity, which has also inspired other studies on plume volume flux [3][4][5][6]. Takata et al used a Reynolds-averaged Navier-Stokes model to predict wind effects on a rising visible plume from an MDCT in the absence of nearby buildings [3], while Fan et al similarly modeled an MDCT near a complex building environment [7]. Chahine et al simulated plume dispersals from four large, collocated natural draft cooling towers to determine the long-range visual impact of the facility [8].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the use of deflectors can reduce the effect of wind on cooling tower operation to a minimum. One can also encounter the results of research on the impact on operation of cooling towers located close to one another and with accompanying industrial facilities [21,22]. The effect of wind on the level of cooling in zones of cooling towers operated in different ways in relation to the wind direction has also been evaluated [23].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [4] conducted a three-dimensional parametric study of the gap between the cooling tower entrance area and the obstacle. Fan and Dong [26] studied the effect of MCTs on the cooling performance of air-cooled condensers in complex environments. Al-Waked [27] studied the effect of wind on the performance of the cooling tower and concluded that a separate cooling tower has better performance than a cooling tower with buildings around it.…”
Section: Introductionmentioning
confidence: 99%